Adaptation in action: Plant defense dynamics in Triticum aestivum L. challenged by chemical elicitors - Riddhi, M; Shirali, A; Meshwa, P; Miral, P; Deepak, A; Monisha, K (Plant Science Today, 2026)
The present study was carried out with the aim of (i) evaluating the effect of chitosan on the free radical scavenging activity, ferric reducing antioxidant power (FRAP) activity, 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity and chitinase activity in T. aestivum L. and (ii) evaluating the effect of different concentration of chitosan on enzyme activities such as phenylalanine ammonia-lyase (PAL) activity and beta- 1, 3-glucanase activity in T. aestivum L. To achieve these goals, the 15-days-old wheat seedlings were treated with different concentrations of chitosan, such as 1-4 mg/mL and further, the enzyme assays were carried out. The results obtained showed that treatment with 0.5 mg/mL of chitosan induced the maximum free radical scavenging activity and DPPH activity in the plant, while treatment with 1.0 mg/mL of chitosan induced the maximum FRAP activity. The response of wheat seedlings to an increase in oxidative stress was correlated with chitosan treatment. Additionally, treatment with 1.0 mg/mL of chitosan to the plant also showed maximum chitinase enzymatic activity in wheat seedlings. Chitosan treatment also elicited enzyme activities such as PAL and beta-1, 3-glucanases. Different concentrations of chitosan treatment showed increasing patterns of PAL activity from 0 hr, which peaked between 24 - 48 hr and thereafter, started decreasing post 72 hr. Similarly, chitosan treatments in wheat seedlings showed an increasing activity of beta-1, 3-glucanase from 0 hr till 48 hr and started decreasing at 72 hr. Overall, the findings showed that chitosan exhibits a protective nature against oxidative stress.